2015
DOI: 10.1186/s12885-015-1787-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of web-based cognitive behavioral therapy for severely fatigued breast cancer survivors (CHANGE-study): study protocol

Abstract: BackgroundAbout one third of breast cancer survivors suffer from persistent severe fatigue after completion of curative cancer treatment. Face-to-face cognitive behavioral therapy (F2F CBT), especially designed for fatigue in cancer survivors, was found effective in reducing fatigue. However, this intervention is intensive and treatment capacity is limited. To extend treatment options, a web-based version of CBT requiring less therapist time was developed. This intervention is aimed at changing fatigue-perpetu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 62 publications
0
49
0
Order By: Relevance
“…23,24 This study found that even patients with a KPS of 40% received some type of treatment despite the patient's lower FC and increased propensity to poorer QoL. 2,7 Therefore, quantification of physical function is becoming an important element in the verification of health--related QoL, considering that cancer is often associated with decreased physical capacity, which interferes with daily activities, especially for those with metastases. [23][24][25] Most patients in our study had metastases, mainly locoregional, which is similar to findings by Montazeri et al 25 that patients with advanced cancer may have poorer QoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 This study found that even patients with a KPS of 40% received some type of treatment despite the patient's lower FC and increased propensity to poorer QoL. 2,7 Therefore, quantification of physical function is becoming an important element in the verification of health--related QoL, considering that cancer is often associated with decreased physical capacity, which interferes with daily activities, especially for those with metastases. [23][24][25] Most patients in our study had metastases, mainly locoregional, which is similar to findings by Montazeri et al 25 that patients with advanced cancer may have poorer QoL.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to new technologies and treatments, the number of women living with the disease increases every year, which explains the growing interest in quality of life (QoL) of breast cancer patients. [1][2][3][4][5] The number of breast cancer survivors is increasing around the world; thus, it is important to improve the health-related QoL of this population. Ability to perform daily activities, patient satisfaction and levels of functionality are all essential to determining QoL in breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…16 Based on a study that examined the efficacy of a minimal intervention for patients with medically unexplained chronic fatigue, we assumed a clinically relevant difference in fatigue severity between the intervention and control condition of 6 points. 16 Based on a study that examined the efficacy of a minimal intervention for patients with medically unexplained chronic fatigue, we assumed a clinically relevant difference in fatigue severity between the intervention and control condition of 6 points.…”
Section: Discussionmentioning
confidence: 99%
“…16 The RCT was reviewed and approved by the Arnhem-Nijmegen Medical Research Ethics Committee (NL43781.091.13) and the ethics committees of the participating hospitals. After 6 months, participants completed the second assessment online.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation